Addition of Six New Genera to the Flora of Odisha: A Report - Mishra, Ramakanta; Jena, Gouri Sankar Juga Prakash; Nayak, Smaranika; Satapathy, Kunja Bihari; Mohapatra, Ashirbad (Asian Journal of Biological and Life Sciences, 2020)
In the present study six genera of plants were recorded as new additions to the angiospermic flora of Odisha state, India along with their detailed description, phenology and distribution. During the extensive exploration in different districts of the state, Calystegia sepium (L.) R.Br. (Convolvulaceae), Cymbalaria muralis G.Gaertn., B.Mey. and Scherb. (Plantaginaceae), Gloxinia perennis (L.) Druce (Gesneriaceae), Fumaria indica (Hausskn.) Pugsley (Papaveraceae), Lobularia maritima (L.) Desv. (Brassicaceae), Tacca leontopetaloides (L.) Kuntze (Dioscoreaceae) were collected and after a thorough microscopic observation and detailed review of the available literature and references, these six genera were found to be new records for the flora of Odisha state, India. Now-a-days, in all over the globe, plant diversity is not only being depleted but also some species are found to become threatened and endangered and more so, many of the natural vegetation become extinct in course of time. A detailed and thorough scientific approach was made on the proper status of these six new recorded genera and discussed in details for their taxonomical, nomenclatural, biological and ecological data (i.e. accepted scientific name, synonyms, geographical distribution and conservation status).
Keywords: New report; Odisha; Phytodiversity